2019
DOI: 10.1074/jbc.ra119.007555
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β/TNF-α/IL-6 inflammatory cytokines promote STAT1-dependent induction of CH25H in Zika virus–infected human macrophages

Abstract: Zika virus (ZIKV) 3 is an enveloped, single-stranded, positive-sense RNA virus of the Flaviviridae family that has emerged as a public health threat because of its global transmission and link to microcephaly. Currently there is no vaccine for this virus. Conversion of cholesterol to 25-hydroxycholesterol by cholesterol 25-hydroxylase (CH25H) has been shown to have broad antiviral properties. However, the molecular basis of induction of CH25H in humans is not known. Elucidation of signaling and transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…A previous research observed high CH25H expression in specifically vulnerable brain regions in patients with Alzheimer's disease [31]. Interestingly, CH25H was induced by proinflammatory cytokines IL-1β, TNF-α, and IL-6 [32]. As a hydroxylating enzyme, CH25H converts cholesterol into 25-hydroxycholesterol (25HC), which contributed to cerebral inflammation, and significantly recruited Iba-1-positive microglia, caused oligodendrocyte apoptosis, and amplified the production of pro-inflammatory and TLRinduced cytokines [33].…”
Section: Discussionmentioning
confidence: 76%
“…A previous research observed high CH25H expression in specifically vulnerable brain regions in patients with Alzheimer's disease [31]. Interestingly, CH25H was induced by proinflammatory cytokines IL-1β, TNF-α, and IL-6 [32]. As a hydroxylating enzyme, CH25H converts cholesterol into 25-hydroxycholesterol (25HC), which contributed to cerebral inflammation, and significantly recruited Iba-1-positive microglia, caused oligodendrocyte apoptosis, and amplified the production of pro-inflammatory and TLRinduced cytokines [33].…”
Section: Discussionmentioning
confidence: 76%
“…6 Catalyzed by activated Janus tyrosine kinase (JAK), STAT is phosphorylated and forms activated dimers, which then enter the nucleus combining with targeted DNA motifs to regulate gene transcription and participate in a variety of physiological or pathological processes. 24 Considering that the phosphorylation of STAT1 occurs at the early stage after macrophages are appropriately stimulated, 25,26 we chose to test the levels of P-STAT1 at 0.5 hours/1 hour after stimulation. Many studies have clarified the relationship between oxidative stress and STAT1 in different aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct role of IP-10 in ZIKV urogenital tract infection has yet to be studied. In addition, other studies in human macrophages have described the ability of ZIKV to upregulate pro-inflammatory cytokines that are responsible for induction of anti-viral proteins, such as CH25H [ 73 ]. However, one limitation of this study includes using PNT1a cells for assessing cytokine production.…”
Section: Discussionmentioning
confidence: 99%